Pengaruh Leverage, Likuiditas, dan Profitabilitas Terhadap Kesulitan Keuangan - Indrati, Menik; Azizah, Intan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of leverage, liquidity, and profitability on financial difficulties. The sample used is the retail sub-sector companies listed on the Indonesia Stock Exchange for 2018–2020. The sample used the purposive sampling method and obtained as many as 13 companies from a total observation of 26 companies. SPSS (Statistical Program for Social Science) data processing application software was used to test hypotheses using a multiple linear regression analysis model. The results showed that leverage had a positive effect on financial difficulties. Liquidity has a negative effect on financial difficulties. Profitability has a negative effect on financial difficulties. This research can be considered in making investment decisions by assessing each financial ratio and other information for accuracy in investing funds and getting the desired return. Companies need to maintain leverage ratios at a reasonable level and not too high, maintain liquidity ratios, and keep their activities at a high enough level to avoid financial difficulties and increase their ability to generate profits.